AWS Solutions architect professional course. (Pragmatic AI Solutions, 2022)
Learn to pass the AWS Solutions Architect Professional Exam. Hello, my name is Noah gift, and I'll be your instructor. This course is AWS Certified Solutions Architect or SAP, co one, a bit of my background. I've worked for approximately 25 years in technology, written multiple books, and I've been certified on multiple AWS exams, and helped develop exams as well as an SME. One of my goals is to teach you to pass the challenging Solutions Architect exam. Let's go through an overview. First up, we have one tool point, 5% in this domain, for organizational complexity. In domain two, we have designed new solutions; this is about a third of the exam. In domain three, we have migration planning 15% domain for cost control, which is about 12 and a half percent, and then domain five will be continuous improvement, or Kaizen is a term I like to use. Let's go ahead and take a look at some of these domains at a very, very high level. So first up, in terms of design for organizational complexity, you're going to need to know things like cross-account authentication, and access strategies, how to design networks, how to prepare for the multi-account; in domain two, you're going to cover security requirements controls when designing and implementing a solution also, about how to design and implement solutions. And then in in terms of business continuity, and performance objectives, those those are the things you're going to be taking care of. Now, in domain three, you'll talk about migration planning. So how do you take an existing workload, move it to the cloud, speak a few migration tools and cloud architecture for a current solution? In domain four, you're going to go into cost control. So what are the pricing models? What are some design controls? And also, how do you identify opportunities to reduce cost? In domain five, this would be a continuous improvement for existing solutions. So how to troubleshoot, maintain different troubleshooting strategies, develop performance metrics for applications and improve the security of existing solutions. So you can see there are a lot of domains here that we're going to cover and let's go ahead and get started. Domain 1: Design for Organizational Complexity Domain 2: Design for New Solutions Domain 3: Migration Planning Domain 4: Cost Control Domain 5: Continuous Improvement.